PERAN MODERNISASI TEKNOLOGI INFORMASI PERPAJAKAN TERHADAP MOTIVASI KERJA PEGAWAI KPP PRATAMA WONOCOLO SURABAYA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2013)
Some forms of taxation information technology modernization improvements that have been made by the DGT include e-system and DGT Information Systems (SIDJP). Implementation of the modernization is expected to reduce the burden of tax officials work. The purpose of this study was to determine whether the modernization of the taxation information technology have contributed to employee motivation KPP Pratama Wonocolo Surabaya. A total population of 84 people and the tax officials to use sampling techniques to obtain the total number of samples. Data analysis technique used is Partial Least Square (PLS). The research proves that the hypothesis is accepted. Modernization of information technology have contributed to employee motivation KPP Pratama Wonocolo Surabaya.